Preparation of a noise map in the center of the Esmeraldas canton (Innovation & Development in Engineering and Applied Science, 2022)
In the present investigation, the noise analysis is carried out on Bolívar street, which is located in the center of the city of Esmeraldas. The study area was established in locations where there are no buildings that block or interrupt noise waves, which is why eight corners along the street are taken. We proceeded to search for information about noise pollution in cantonal, provincial, national, and international studies, in order to collect information regarding the problem, regulations, and methodologies that are the basis of the investigation. When obtaining the results of the monitoring, the proposal was made for the creation of a noise map, taking into account the methodology for the processing and manipulation of information in the Qgis software. Statistical and cartographic analysis was carried out to obtain the results on the lifting of the noise map with respect to the permissible levels according to land use.